COVID-19 in Cyanotic Congenital Heart Disease - Lama A Ammar; Joseph E Nassar; Fadi Bitar; Mariam Arabi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Congenital heart disease (CHD) is the most prevalent congenital defect in newborn infants. Due to the various types of heart abnormalities, CHD can have a wide range of symptoms. Cardiac lesions comprise a range of different types and accordingly varying severities. It is highly helpful to classify CHD into cyanotic and acyanotic heart diseases. In this review, we are investigating the course of Coronavirus disease 2019 (COVID-19) in cyanotic CHD patients. The infection may directly or indirectly affect the heart by affecting the respiratory system and other organs. The effect on the heart that is pressure- or volume-overloaded in the context of CHD is theoretically more severe. Patients with CHD are at a higher risk of mortality from COVID-19 infection or suffering worse complications. While the anatomic complexity of CHD does not seem to predict the severity of infection, patients with worse physiological stages are more susceptible such as cyanosis and pulmonary hypertension. Patients with CHD exhibit continuous hypoxemia and have lower oxygen saturations because of a right-to-left shunt. Such individuals run the danger of rapidly deteriorating in the event of respiratory tract infections with inadequate oxygenation. Additionally, these patients have a higher risk of paradoxical embolism. Hence, critical care should be given to cyanotic heart disease patients with COVID-19 in comparison to acyanotic patients and this is through proper management, close observation, and adequate medical therapy.